Family presence in emergency: Attitude and belief among emergency health professionals in a Tertiary Care Hospital of Nepal (Health Renaissance, 2017)
Background: The emergency department of B.P Koirala Institute of Health Sciences, Dharan, a  700 bedded tertiary care centre provides all medical and surgical services, with easy access to patients by their family members during most of the resuscitation procedures. Complete privacy hence is not ideally maintained. Coping with emotional stress among the family members can be a gruesome experience and reactions from them can be unpredictable. Hence, health professionals are usually exposed to various emotions of the family members of these sick patients.Methods: It is a descriptive cross sectional study among the health professionals working in the emergency department. A sample size of 80 is taken over a period of 3 months. A semi-structured questionnaire leaflet was distributed and collected by the researcher. The attitude and belief was evaluated by 12 questions on the 5 point Liker scale and cutoff value being 3. Points less than 36 were given as negative attitude towards the family presence and more being positive.Results: Out of 80samples, 75 completed with a response rate of about 94%. The majority belonged to age group 20-29 years (70.7%) age, among profession Nurses respondents were about 56%. Male and Female respondent were about equal in numbers, qualification with undergraduate level was higher (73.3%), with an experience of less than 1year being 40%. Amongst the responders there is a positive attitude with increasing age, experience and qualification.Conclusion: The health professionals had a negative attitude towards the presence of family members during the resuscitation or invasive procedures. Hence with the ethnicity and cultural aspect of family their presence is well accepted. Health Renaissance 2015;13 (3): 152-160